Minimnya Ketersediaan Penjualan Ikan di Pasar MMTC - Budiyanti Budiyanti; Ellma Aggresia Br Purba; Ellsy Nila Sari Situmeang; Dhea Zuhrika (Departement of Mathematics Education, 2024)
The fish market in Medan, Indonesia, is a significant contributor to the local economy, providing an important source of protein for its residents. Fish product suppliers in the Medan MMTC market face challenges in managing inventory levels. The minimal availability of fish for sale at the MMTC market is an important issue that can affect the local economy and food security of local communities. This mini research aims to find out what factors cause the minimal availability of wet fish sales at MMTC as well as the influence of seasonal demand for fish at MMTC on fish availability. This research uses a qualitative approach with a literature review method. Data was collected from articles and journals available on Google Scholar and other websites. Meanwhile, data collection techniques use interviews, observation and documentation. The research results show that the factors causing the minimal availability of wet fish sales at MMTC include: limited resources, increasing costs, changes in consumption patterns, limited infrastructure, and limited markets. In its synthesis, the influence of seasonal demand for fish in the MMTC market on fish availability is influenced by several factors that influence demand for fish in the market, namely: seasonal dynamics in demand for fish in the MMTC market, variability of consumers who buy fish in the MMTC market, and the influence of fish prices